Identification of seawater intrusion based on geochemical data in Pelauw-Kariu Region, Maluku - Rumpakwakra, Ervina; Jaya, Gede Wiratma; Bahri, Samsul; Ramahdan, Aditya; Zulfiah, Zulfiah; Thohirah, Afifah; Taipabu, Muhammad Ikhsan (Brawijaya University, 2024)
Groundwater is utilized as a clean water source including in Pelauw and Kariu Villages. Drilling and excavating are frequent techniques utilized in the construction of wells that serve as sources of groundwater. As a result of the ocean encircling the majority of this area, salinity may infiltrate wells. Consequently, the purpose of this study was to ascertain whether seawater intrusion had occurred in 12 nearby wells. Major ion tests were carried out in the lab, while surveys and measurement fields were carried out for the sampling procedure. Ion Cl, EC, TDS, Simpson ratio, and BEX data are used in the analysis to determine whether seawater intrusion is present. Additionally, the Piper diagram is used to categorize different types of water based on the outcomes of the main ion test. The findings indicated that Cl-, EC, and TDS levels have increased at a number of the sampling sites. At point A09, there is an indication of seawater intrusion based on the BEX values, which shows a negative number. The majority of the well water, as determined by a water classification analysis using the Piper diagram, is of the calcium carbonate type. Meanwhile, the remaining portion is separated into the calcium sulfate and sodium bicarbonate types.